PENERAPAN PENGUKURAN KINERJA DENGAN PENDEKATAN BALANCED SCORECARD PADA PT BANK SUMSELBABEL CAPEM MUARA BELITI - Subianto Subianto; Charli Andri (LPPM Universitas Bina Insan, 2019)
Application of performance measurement with the balanced scorecard approach at PT. Bank SumselBabel Capem Muara Beliti. From a financial perspective, the ROA ratio shows very good results of> 2%. The ROE ratio at PT Bank SumselBabel Capem Muara Beliti cannot be applied because capital is not reflected in the financial statements of sub-branch offices. The LDR ratio in 2017 can be categorized as not good because it is above 85%, which is 161.23% and for 2018 it can be categorized as good because it is below 75%, namely 25.23%. In 2017 the BOPO ratio showed good results because it was below 92% namely 80.64%, but in 2018 BOPO showed poor results because it was> 92% ie 112.39%. The NIM ratio can be categorized as good because it is above 2%, namely 5.65% and the NPL ratio can be categorized as healthy because banks do not have problem loans. The Customer perspective based on the results of the questionnaire calculation using MAM analysis shows a percentage of 11.6668% which means that the customer is very satisfied with the SumselBabel Bank Capem Muara Beliti. Internal Business Process Perspective, the physical services of the SumselBabel Bank Capem Muara Beliti have provided adequate facilities and facilities, while the non-physical service, namely the efficiency of customer service transaction time with customers, is considered quite good at 50% while the efficiency of the time of teller transactions with customers by 95% is very good. In the perspective of learning and growth, the results of the calculation of the questionnaire using MAM analysis showed employees were very satisfied while working at PT Bank SumselBabel Muara Beliti which amounted to 17.867%.